Name-Based Estimators of Intergenerational Mobility - Torsten Santavirta; Jan Stuhler (Institute of Labor Economics (IZA), 2024)
Recent studies use names - first and surnames - to estimate intergenerational mobility in sources that lack direct family links. While generating novel evidence on intergenerational transmission processes, it remains unclear how different estimators compare and how reliable they are. This paper evaluates the most popular name-based methods, using newly digitised records from Finland and U.S. Census data. We illustrate that their interpretation depends on sampling properties of the data, such as the overlap between the parent and child samples, which differ widely across studies. We correct for the attenuation bias from limited overlap and address other common problems encountered in applications.
Keywords: J62; 330; intergenerational mobility; names; grouping estimator; split-sample IV